Birth weight classification in gestational diabetes: is there an ideal chart? - Silveira Mastella, Livia; Weinert, Letícia Schwertz; Gnielka, Vanessa; Hirakata, Vânia Naomi; Oppermann, Maria Lúcia Rocha; Silveiro, Sandra Pinho; Reichelt, Angela Jacob (Clinical and Biomedical Research, 2017)
Introduction: Gestational diabetes mellitus (GDM) is associated to increased rates of large for gestational age newborns and macrosomia. Several charts are used to classify birth weight. Is there an ideal chart to classify newborns of GDM mothers? Methods: We evaluated adequacy of birth weight of 332 neonates born to GDM mothers at Hospital de Clínicas de Porto Alegre, Brazil. Newborns were classified according to gestational age as small (SGA), adequate or large (LGA) based on four charts: Alexander, Pedreira, INTERGROWTH 21st Project and SINASC-2012. The latter was built using data from a large national registry of 2012, the Born Alive National Surveillance System (Sistema de Informações de Nascidos Vivos – SINASC), which included 2.905,789 birth certificates. Frequencies of SGA and LGA and Kappa agreement were calculated. Results: In non-gender adjusted curves, SGA rates (95% confidence interval) varied from 8% (5-11) to 9% (6-13); LGA rates, from 11% (8-15) to 17% (13-21). For males, SGA rates varied from 3% (1-6%) to 6% (3-11%), and LGA rates, from 18% (13-24%) to 31% (24-38%); for female, SGA rates were from 3% (1-7%) to 10% (6-16%) and LGA rates, from 11% (6-16%) to 19% (13-26%). Kappa results were: ALEXANDER vs. SINASC-2012: 0.80 (0.73-0.88); INTERGROWTH 21st vs. SINASC-2012 (adjusted by sex): 0.62 (0.53-0.71); INTERGROWTH 21st vs. PEDREIRA: 0.71 (0.62-0.79); SINASC-2012 (by sex) vs. PEDREIRA: 0.86 (0.79-0.93). Conclusions: Misclassification has to be taken into account when evaluating newborns of GDM mothers, as LGA rates can almost double depending on the chart used to classify birth weight.